Atrial dysfunction: a contrast-free marker for HFpEF in obese diabetics—insights from comprehensive CMR and serum biomarker analyses - Rebecca Elisabeth Beyer; Maximilian Leo Müller; Patrick Doeblin; Stefanie Maria Werhahn; Amedeo Chiribiri; Carsten Tschöpe; Smita Sampath; G. Brandon Atkins; Dawn Cislak; An Bautmans; John Palcza; Tom McAvoy; et al. (Cardiovascular Diabetology)
Abstract Background The diagnostic criteria for HFpEF remain inconsistently defined, further confounded by comorbidities such as obesity and type 2 diabetes mellitus (T2DM), which are thought to contribute to its pathogenesis via chronic pro-inflammatory mechanisms. This study aimed to evaluate the relationship between advanced cardiac magnetic resonance (CMR) imaging and pro-fibrotic and inflammatory serum biomarkers, assessing their potential to discriminate HFpEF from associated comorbid conditions. Methods This was an exploratory analysis of a prospective cohort study of 35 obese/overweight participants (mean age 64 ± 8 years, 23% females), including 16 with T2DM, 13 with HFpEF (NYHA II–III) and T2DM, and 6 healthy controls. All subjects underwent comprehensive contrast-enhanced CMR at a 3 T scanner (Philips Ingenia, The Netherlands), including assessment of left ventricular and left atrial (LA) volumetry and function, myocardial perfusion reserve (MPR), and diffuse fibrosis imaging (ECV). Obtained serum biomarkers were Pentraxin-3, Galectin-3 and Interleukin-1 Receptor-Like 1 (IL1RL1). Statistical analyses included one-way ANOVA, Tukey test, Pearson’s correlation, regression and receiver operating characteristic analyses, and intra-class correlation. Results In multivariable regression, impaired measures of LA structure and function emerged as the only independent discriminators of HFpEF, with LA maximum volume showing an OR of 1.13 (95% CI 1.05–1.28), reservoir strain of 0.71 (95% CI 0.44–0.89), conduit strain of 0.57 (95% CI 0.32–0.82) and booster strain of 0.70 (95% CI 0.48–0.89) per unit increase. No differences in MPR nor ECV were observed between the groups. While serum biomarkers Galectin-3 and Pentraxin-3 were significantly higher in HFpEF vs. obese controls (16.1 ng/ml ± 3.8 ng/ml vs. 10.6 ng/ml ± 3.7 ng/ml, p = 0.011, and 0.84 ng/ml ± 0.67 ng/ml vs. 0.21 ng/ml ± 0.05 ng/ml, p = 0.031, respectively), these biomarkers remained within normal limits and showed only moderate correlations with CMR metrics. Highest inter-study reproducibility was seen in MPR (ICC: 0.94), LA Reservoir Strain (ICC: 0.84) and serum biomarkers (ICC: 0.087–0.93). Conclusion CMR markers of diffuse fibrosis and microvascular dysfunction may not differentiate HFpEF from obese or diabetic controls. However, left atrial function assessment may evolve to be a reproducible and practical CMR marker, effectively distinguishing HFpEF independent of fibrotic remodeling.